A Study on the Leading Power of Ideological and Political Courses in Higher Education Institutions towards Social Thoughts from the Perspective of Economic Narrative - Fu, Dongmei (International Journal of Global Economics and Management, 2024)
In the digital age, the diversification of social thoughts brings up new challenges to the dominant position of socialist ideology, and also puts forward new requirements for ideological and political courses in universities. Consolidating and developing socialist ideology, and enhancing the leadership of ideological and political courses in social thoughts require new ideas. The article attempts to innovate the narrative teaching method of ideological and political courses from the perspective of "economic narrative"; Dig deep into economic practice cases and construct the narrative logic of socialist economy; Utilize the advantages of online communication to cultivate the narrative logic of socialist economy.